Pemberdayaan Bumdes dalam Pengadaan Alsintan untuk Meningkatkan Perekonomian Petani Desa - Dharodjah, Ulya; Arif, Zainul; Akbar, Jamaluddin; Wahib, Khadimul; Adigara, Angga (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Agriculture is an important sector in rural areas. However, in Karang Duwak Village, Arosbaya District, farmers still use conventional methods in the agricultural process. This results in high production costs because farming businesses mostly use farm labor, which then leads to a decrease in farmers' income. Therefore, modernization in the agricultural sector is needed to increase agricultural productivity and efficiency, involving BUMDes as a driving force in strengthening the village's potential. This research was conducted using qualitative methods through observation and interviews to obtain concrete data on the agricultural conditions in the village. Then, community service activities were carried out through the empowerment of BUMDes Karang Duwak Village in the procurement of agricultural machinery for farmers. The results of the activities showed that after using agricultural machinery, the production costs of farming businesses were reduced, the time required for the agricultural process became faster, and farmers' income increased. Farmers can increase their agricultural business capital from the profits obtained and purchase better quality rice seeds. With greater capital and better seeds, the quality of agricultural products will also improve. A good harvest will increase farmers' income and improve the economy of the village farmers. BUMDes, together with village officials and the community, worked together in the procurement and supervision of agricultural machinery use, and were responsible for maintaining the agricultural machinery so that it could be used to develop agriculture in a sustainable manner.